Using Orthosiphon stamineus B. for phytoremediation of heavy metals in soils amended with sewage sludge - Abdu, Arifin; Aderis, Najihah; Abdul Hamid, Hazandy; Nik Ab. Majid, Nik Muhamad; Jusop, Shamsuddin; Karam Singh, Daljit Singh; Ahmad, Khairulmazmi (Science Publications, 2011)
Problem statement: Phytoremediation is a biological treatment where plants are used to remove pollutants from the environment to make them harmless. A study was conducted in a greenhouse at the Faculty of Forestry, Universiti Putra Malaysia on the potential of Orthosiphon stamineus B. planted in sewage sludge for heavy metals uptake. The objective of this study was to evaluate the ability of O. stamineus to remove toxic heavy metals from sewage sludge. Approach: A total of 36 of O. stamineus were treated at six different levels of soil mixture and sludge treatment including one control. The treatments were replicated six times. Growth parameters mainly height and basal diameter were measured for each plant within 10 weeks. Soil texture (pipette method), soil pH (glass-electrode method) and total carbon (C) (Los on Ignition) were determined. The concentration of heavy metals that include cadmium (Cd), chromium (Cr), zinc (Zn), copper (Cu) and lead (Pb) in the planting media and plant parts were analyzed using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). Results: There was a significant difference (P≤0.05) in height, basal diameter and number of leaves among the six treatments. The height increment values for all treatments in descending order are: T3 (10.22 cm), T2 (12.42 cm), T1 (13.92 cm), T5 (14.65 cm), T4 (16.20 cm) and C (16.97 cm). In terms of basal diameter, the highest incremental values in ascending order are T5 (0.99 mm), T1 (1.20 mm), T3 (1.31 mm), T2 (1.38 mm), T4 (1.53 mm) and C (1.75 mm). Soil texture for the control is categorized as clay and for T5 is silt loam. Soil reaction is acidic while total carbon ranges from 16.7% to 61.3 %. The concentrations of heavy metals in the planting medium were higher before planting as compared to after planting. For examples, the values for Cd, Cr, Zn, Cu and Pb in T5 (100% sewage sludge) before planting are 0.18 ppm, 23.45 ppm, 290.05 ppm, 17.07 ppm and 5.33 ppm, respectively. The values decreased after planting where 0.13 ppm for Cd, 24.30 ppm for Cr, 252.04 ppm for Zn, 18.56 ppm for Cu and 5.96 ppm for Pb were observed. O. stamineus absorbed heavy metals in the range of 0.01 ppm to 0.57 ppm for Cd, 0.08 ppm to 8.48 ppm for Cr, 0 ppm to 43.93 ppm for Zn, 0.11 ppm to 16.73 ppm for Cu and 0.01 ppm to 9.05 ppm for Pb in various plant parts of leaves, stems and roots. Conclusion: Most of the heavy metals taken up by the plants were stored in the leaves, whereas Zn seemed to be stored in all plant parts. These results indicate that O. stamineus has the potential to accumulate heavy metals particularly Zn, Pb and hence could be considered as a good phytoremediator species.